Neurovestibular Symptoms in Astronauts Immediately after Space Shuttle and International Space Station Missions - Reschke, Millard F. (OTO Open, 2017)
OBJECTIVES: (1) To assess vestibular changes and related sensorimotor difficulties, especially instability of posture and gait, among astronauts immediately after they return from space and to compare the effects experienced after short- and long-duration space missions. (2) To determine whether any difficulties experienced were severe enough to impair the astronauts’ ability to leave the spacecraft in the event of an emergency. STUDY DESIGN: Prospective cohort study. SETTING: National Aeronautics and Space Administration’s Kennedy Space Center and Johnson Space Center. SUBJECTS AND METHODS: Fourteen crewmembers of 3 Space Shuttle missions that lasted about 1 week and 18 crewmembers of 8 International Space Station missions that lasted about 6 months were given brief vestibular examinations 1 to 5 hours after landing. These examinations focused on the presence of vestibular and motor coordination difficulties, as well as motion sickness and motion sensations. Standardized tests included the observation of abnormal eye movements, finger-to-nose pointing, standing up from a seated position, postural stability, and tandem gait. RESULTS: Unsteady walking and postural instabilities were observed after short- and long-duration missions. Motion sickness symptoms were observed after long-duration missions but not after short-duration missions. The symptom most frequently reported by the astronauts was an exaggerated perceived motion associated with sudden head movements during reentry and after landing. CONCLUSION: The severity of the observed abnormalities would limit the ability of crewmembers during the first 5 hours after landing and increase the time required to leave the spacecraft during this period.